Variation of carbon, nitrogen and phosphorus content in fungi reflects their ecology and phylogeny - Pánek, Matěj; Vlková, Tereza; Michalová, Tereza; Borovička, Jan; Tedersoo, Leho; Adamczyk, Bartosz; Baldrian, Petr; Lopéz-Mondéjar, Rubén (Frontiers in Microbiology, 2024)
Fungi are an integral part of the nitrogen and phosphorus cycling in trophic networks, as they participate in biomass decomposition and facilitate plant nutrition through root symbioses. Nutrient content varies considerably between the main fungal habitats, such as soil, plant litter or decomposing dead wood, but there are also large differences within habitats. While some soils are heavily loaded with N, others are limited by N or P. One way in which nutrient availability can be reflected in fungi is their content in biomass. In this study, we determined the C, N, and P content (in dry mass) of sporocarps fruiting bodies of 214 fungal species to inspect how phylogeny and membership in ecological guilds (soil saprotrophs, wood saprotrophs, and ectomycorrhizal fungi) affect the nutrient content of fungal biomass. The C content of sporocarps fruiting bodies (415 ± 25 mg g -1 ) showed little variation (324-494 mg g -1 ), while the range of N (46 ± 20 mg g -1 ) and P (5.5 ± 3.0 mg g -1 ) contents was within one order of magnitude (8-103 mg g -1 and 1.0-18.9 mg g -1 , respectively). Importantly, the N and P contents were significantly higher in the biomass of soil saprotrophic fungi compared to wood saprotrophic and ectomycorrhizal fungi. While the average C/N ratio in fungal biomass was 11.2, values exceeding 40 were recorded for some fungi living on dead wood, typically characterized by low N content. The N and P content of fungal mycelium also showed a significant phylogenetic signal, with differences in nutrient content being relatively low within species and genera of fungi. A strong correlation was found between N and P content in fungal biomass, while the correlation of N content and the N-containing fungal cell wall biopolymer chitin showed only weak significance. The content of macronutrients in fungal biomass is influenced by the fungal life style and nutrient availability and is also limited by phylogeny.